Dealing with uncertainties in policing serious crime - Bammer, Gabriele (ANU E Press, 2010)
Grappling with uncertainties is at the heart of investigating serious crime. At a time when such crime is becoming more complex and resources are increasingly stretched, this book draws together research and practice perspectives to review fruitful approaches to uncertainties and to chart the way forward. Scene setting chapters describe the consequences of globalisation and the spread of sophisticated information technologies (Sue Wilkinson), as well as advances in understanding and managing uncertainty (Michael Smithson). Ways of enhancing responses from statistics (Robyn Attewell), risk analysis (Richard Jarrett and Mark Westcott) and the psychology of decision making (Mark Kebbell, Damon Muller and Kirsty Martin) follow. These are complemented by insights from law (the Hon. Tim Carmody SC), politics (the Hon. Carmen Lawrence) and business (Neil Fargher), which all have significant intersections with policing. Synthesis is provided by the four final chapters which present the outlooks of the investigating officer and investigation manager (Peter Martin), the provider of policing higher education (Tracey Green and Greg Linsdell), the capacity-building consultant (Steve Longford), and the leader of a law enforcement agency (Alastair Milroy).
Keywords: Criminal justice, Administration of -- Australia.; Evidence, Criminal -- Australia.; Burden of proof -- Australia.; Criminal investigation -- Australia.; Criminal law -- Australia.; Justice pénale -- Administration -- Australie.; Preuve (Droit pénal) -- Australie.; Fardeau de la preuve -- Australie.; Enquêtes criminelles -- Australie.; Law.; Laws of Specific jurisdictions.; Criminal law and procedure.; SOCIAL SCIENCE -- Criminology.; Burden of proof; Criminal investigation; Criminal justice, Administration of; Criminal law; Evidence, Criminal; Australia